Cost effectiveness of nutrient retention in constructed wetlands at a landscape level. (15th December 2022) - Djodjic, F.; Geranmayeh, P.; Collentine, D.; Markensten, H.; Futter, M.
Abstract: Since 1990, over 13 000 ha of constructed wetlands (CWs) have been implemented to increase biodiversity and reduce nitrogen (N) and phosphorus (P) loads to Swedish waters. Despite the considerable number of CWs and ambitious investments planned for the coming three years, there is limited follow up of cost-efficiency of catchment- and landscape-scale nutrient retention by existing CWs. Such follow up evaluation could provide clear guidance regarding optimal size and location of future CWs. We present a three-step modelling approach to assess cost-efficiency of 233 CWs in two Swedish regions (East, 4321 km 2, and West, 916 km 2 ). Modelled nutrient retention in CWs was predominantly low, especially in the East, due to their suboptimal location in catchments, e.g., with inadequate upstream areas (low hydraulic loads) and/or low share of arable land (low nutrient loads). Suboptimal location of CWs generates both higher than necessary costs and low area-specific nutrient retention, leading to low cost-efficiency. Some high cost-efficiency CWs were identified, especially for N retention in the West. To increase their cost-efficiency, continued investments in CWs require clear guidance and instructions. To achieve optimal placement, both CW site and size in relation to incoming hydraulic and nutrient loads must be considered. Graphical abstract: Image 1 Highlights: Cost effectiveness of nutrient retention in existing constructed wetlands is extremely variable. Proper placement and size of the constructed wetland in relation to the upstream catchment area increase cost effectiveness. High share of arable land in the catchment further increases cost effectiveness. Model can easily be up-scaled to improve optimal placement and size of future wetlands.